Perception of Organizational Culture a Case Study: Exploring the Relationship between Background Variables and Employee Commitment in Organizational Culture (Journal of Advances and Scholarly Researches in Allied Education, 2012)
An attempt has been made toexamine the relationship of background variables such as age, gender, maritalstatus, education, work experience in present organization, work experience inpresent position and total work experience with employees’ commitment. In thisstudy, the researcher has developed suitable measures for OC, and the items forEC has been adopted from the scale developed by Allen and Mayer (1990). Theresearcher has picked out eight dimensions for OC and three dimensions for EC.Reliability test have been conducted for OC and EC. The questionnaire has beenused to collect qualitative data from the employees. This qualitative data havebeen utilized to present the case study of the organization.